The Acts of the Apostles - Hamm, M. Dennis (Collegeville, Minn. : Liturgical Press, 2005)
"Complete biblical texts with sound, scholarly based commentary that is written at a pastoral level; the Scripture translation is that of the New American Bible with Revised New Testament and Revised Psalms (1991)"--Provided by publisher.
Includes index.
Keywords: Bible. -- Commentaries